Investigations of low-cement castables with shamotte aggregate/Mažacemenčio kaitrai atsparaus betono su šamoto užpildu tyrimai - Goberis, Stasys; Merlinskaja, Liutauras; Pundienė, Ina (Journal of Civil Engineering and Management, 1999)
The castables with low-cement and normal quantity cement in its composition physical and mechanical properties was investigated. Aggregates of recycled shamotte waste, which are characterised by high water absorption, were used for castables. The results of influence of firing temperature on density and cold crushing strength for three series castables were determined (Fig 1 and 2). Thermal shock resistance, bending strength and deformations of the castables were investigated additionally (Table 2 and Fig 4). The results of investigations showed the advantage of low-cement castables: better thermal shock resistance, higher cold crushing and bending strength after firing at high temperature. The properties of developed low-cement and traditional castables produced with schamotte waste aggregates were compared with the data from German, Danish and Polish castables, a special quality shamotte aggregate was used (Table 1). Low-cement castable based on shamotte waste aggregates were developed and used for producing “Ipsen” furnace lining items.Article in Lithuanian.First Published Online: 26 Jul 2012